2008
DOI: 10.1017/s0959270908000403
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of research to conservation action for the Northern Bald Ibis Geronticus eremita in Morocco

Abstract: The Northern Bald Ibis or Waldrapp Geronticus eremita is a species of arid semi-deserts and steppes, which was formerly widely distributed as a breeding bird across North Africa, the Middle East and the European Alps. Just over 100 breeding pairs now remain in the wild at two sites in Morocco whilst two further wild pairs remain in Syria. There is also a population in Turkey, which is maintained for part of the year in captivity, and a large captive population in zoos. The species is classified by IUCN as ‘Cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(82 citation statements)
references
References 11 publications
5
77
0
Order By: Relevance
“…The distances of key feeding grounds from both nesting sites in Syria (Serra et al 2008) are comparable to those reported in the literature relating to Turkey and Morocco (Hirsch 1979;Bowden et al 2008). The feeding areas used by ibises at their breeding grounds are heavily degraded in line with the general ecological degradation of the Syrian desert (Serra et al 2008).…”
Section: Nesting Habitatsupporting
confidence: 74%
See 2 more Smart Citations
“…The distances of key feeding grounds from both nesting sites in Syria (Serra et al 2008) are comparable to those reported in the literature relating to Turkey and Morocco (Hirsch 1979;Bowden et al 2008). The feeding areas used by ibises at their breeding grounds are heavily degraded in line with the general ecological degradation of the Syrian desert (Serra et al 2008).…”
Section: Nesting Habitatsupporting
confidence: 74%
“…Human disturbance was recorded as having negative effects on the Northern Bald Ibises breeding both in Turkey and in Morocco (Hirsch 1976;Collar and Stuart 1985;Bowden and Smith 1997;Bowden et al 2008), along with raven depredation (Bowden et al 2003(Bowden et al , 2008. A marked sensitivity to human disturbance at breeding sites versus at roosting sites outside the breeding season was described by Bowden and Smith (1997).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The doubling of the number of nesting pairs that laid eggs, from 77 pairs (1996) [14] to 111 pairs (2016) [15], should be followed by an expansion of the breeding sites at the northern edges of the known breeding range in southwest Morocco. The lack of suitable nesting sites between Tamri and Cap Ghir, 37 km northwest to Agadir, may explain the trend of northward expansion.…”
Section: Onmentioning
confidence: 99%
“…The species remains very vulnerable to any one-off disasters due to the social behaviour complexity of the species, which breeds colonially and usually feeds in groups, and to the reduced population size [14]. The SMNP has been created in 1991 to protect these remnant ibis colonies.…”
mentioning
confidence: 99%